CYFIP1 gene expression in umbilical cord blood and its relationship with maternal body mass index - Mahsa Eskandari; Elham Hosseini; Zahra Zandieh; Ehsan Noori; Raheleh Kafaeinezhad; Mansour Sadeghzadeh; Ali Awsat Mellati (Mashhad University of Medical Sciences, 2024)
Introduction: The present study was conducted with aim to investigate the expression of the CYFIP1 gene in the umbilical cord blood (UCB) of newborns and its possible relationship with different categories of pre-pregnancy maternal body mass index (BMI), lipid profile, birth weight and infant status for gestational age.Methods: This cross-sectional study was conducted from 2020 to 2021 on UCB of 118 male newborns from Mousavi and Bahman hospitals in Zanjan. According to pre-pregnancy BMI, women were divided into three groups: normal, overweight and obese. Each UCB sample was divided into two parts. A part was used to analyze the lipid profile including low-density lipoprotein (LDL), triglyceride (TG), total cholesterol (TC) and high-density lipoprotein (HDL). mRNA extraction of peripheral blood mononuclear cells was performed to investigate the expression of CYFIP1 gene. Data were analyzed using SPSS statistical software (version 21) and Pearson's correlation test. P<0.05 was considered statistically significant.Results: The expression of the CYFIP1 gene was elevated in UCB from women classified as overweight or obese compared to those with normal weight (p=0.001). UCB of obese women exhibited higher cholesterol and LDL levels compared to normal-weight and overweight women (p=0.001). Positive correlations were observed between pre-pregnancy maternal BMI and cord blood CYFIP1 gene expression (r=0.333, p=0.0001), as well as cholesterol (r=0.520, p=0.0001), TG (r=0.290, p=0.001), LDL (r=0.397, p=0.0001), and birth weight of infants categorized based on gender and gestational age (r=0.262, p=0.001).Conclusion: Increased expression of CYFIP1 gene is correlated positively with different categories of pre-pregnancy BMI and lipid profile, implying that regarding the role of CYFIP1 gene in brain development, the risk factors contributing to increasing BMI may have negative consequences on fetal health and development.